Boron Adsorption Equilibrium in Soils - Bhatnagar, R S; Attri, S C; Mathur, G S; Chaudhary, R S (Annals of Arid Zone, 2016)
Boron equilibrium in the Soils of Rajasthan Canal area was studied. The adsorption of boron is found to depend upon the texture of soils. There exists always an equilibrium between adsorbed and SQil solution boron. Freundlich adsorption iS0lherm is valid for wider range of boron concentrations than Langmuir’s adsorption isotherm. Quadratic curve could not be finally treated as an usual form of multimolecular adsorption isotherm for these soils. The free molar energy was more for finer soils but it decreases with an increase in boron concentration